Testing the Environmental Kuznets Curve Hypothesis in CEMAC Countries - Ella, Philemon Nsi; Mabiala, Jean Felix; Ikinda, Louis Bertrand Ogoula (Asian Journal of Empirical Research, 2022)
The objective of this study is to test the hypothesis of the environmental Kuznet curve (EKC) for 6 CEMAC countries covering the period 1960-2014. We wanted to know if the evolution of per capita income affects environmental quality in the income-emissions relationship (environment). To achieve this objective, we used the method of fixed effects. The results of this study reveal that there is no empirical support for the presence of an environmental Kuznets curve hypothesis. On the other hand, there is rather an inverted "N"-shaped relationship between gross domestic product per capita and CO2 emissions. Moreover, the use of the FMOLS method gives robust results. For this purpose, the minimum turning point which corresponds to per capita income from which CO2 emissions increase is 89.84 dollars and the maximum point corresponding to per capita income from which CO2 emissions decreases is 116.21 dollars. Therefore, CEMAC countries must undertake income policies with the aim of reaching at least the threshold of 1116.21 dollars per capita in order to reverse the evolution of CO2 emissions.